Emulsifier inclusion in diets with energy reduction for laying hens - Ferreira, Joyce A.; Geraldo, A.; Kaike Valentim, J.; Silva, Elaine A.; Alvarenga Miranda, D.; Lemke, Sara S. R.; Alexandre de Almeida, A.; Mendes, Janaína P. (Cuban Journal of Agricultural Science, 2022)
This study aimed to investigate the effects of different metabolizable energy levels of diets that were supplemented with emulsifier on performance and egg quality of laying hens. The used emulsifier contains mono and diglycerides of fatty acids. Four hundred Hisex Brown laying hens 50 weeks old were randomly assigned to five experimental groups (ten replicates of 8 laying hens each). The division of groups was as follows: positive control diet (PC, 11.620 kJ/kg ME/kg); positive control diet supplemented with an emulsifier (E) in 100 g/t (PC+E); low-energy diets (11.474; 11.328; 11.182 kJ/kg ME/kg) supplemented with E. LED 11.485,08+E low-energy diet LED 11.338,64+E. There was no significant difference for the variables of performance and internal quality where laying hens that received diets with a reduction in energy level ranging from 11.474 kJ/kg to 11.182 kJ/kg of MS. For the external quality characteristics of the eggs, there was a significant effect only on the percentage of the shell. Emulsifier supplementation in diets with different energy levels provides performance and egg quality similar to that of laying hens receiving a balanced diet with the recommended energy levels for the phase. Key words: emulsification, feed energy, hisex brown, lipids